Composition of the intestinal microbiota and its variations between the second and third trimesters in women with gestational diabetes mellitus and without gestational diabetes mellitus - Liu, Nana; Sun, Yin; Wang, Yaxin; Ma, Liangkun; Zhang, Suhan; Lin, Hang (Frontiers in Endocrinology, 2023)
Objective: This study was designed to explore the composition of the intestinal microbiota and its longitudinal variation between the second trimester (T2) and the third trimester (T3) in women with gestational diabetes mellitus (GDM) and pregnant women with normal glucose tolerance. Methods: This observational study was conducted at Peking Union Medical College Hospital (PUMCH). Women with GDM and pregnant women with normal glucose tolerance were enrolled in the study, and fecal samples were collected during T2 (weeks 24~28) and T3 (weeks 34~38). Fecal samples were analyzed from 49 women with GDM and 42 pregnant women with normal glucose tolerance. The 16S rRNA gene amplicon libraries were sequenced to analyze the microbiota and QIIME2 was used to analyze microbiome bioinformatics. Results: The four dominant phyla that Firmicutes, Bacteroidetes, Actinobacteria and Proteobacteria which accomplish about 99 % of the total relative abundance did not significantly change between the T2 and T3 in the GDM and healthy groups. At the genus level, the relative abundance of Scardovia (0 vs. 0.25%, P = 0.041) and Propionibacterium (0 vs. 0.29%, P = 0.041) increased significantly in the control group, but not in the GDM group. At the phylum level, the relative abundance of Firmicutes and Actinobacteria was significantly different between women with GDM and pregnant women with normal glucose tolerance in both T2 and T3. In T2 and T3, the relative abundances of unidentified_Lachnospiraceae, Blautia, and Parabacteroides were significantly higher in the GDM group than in the control group (P<0.05). The relative abundance of Bifidobacterium in the GDM group was lower than in the control group in both T2 and T3. Conclusions: The intestinal microbiota composition was stable from T2 to T3 in the GDM and control groups; however, the intestinal microbiota composition was different between the two groups.